2012
DOI: 10.1590/s1516-14392012005000129
|View full text |Cite
|
Sign up to set email alerts
|

Cement mixtures containing copper tailings as an additive: durability properties

Abstract: The effects of copper tailings as an additive, on some durability properties of cement mixtures were investigated. In each mixture, copper tailings addition levels by mass were 0%, 5% and 10%. Compared to the control samples, copper tailings blended pastes showed superior performance against autoclave expansion while insignificant decreases in sulfate resistance of mortars were observed. Copper tailings increased the water absorption and total permeable voids of concretes slightly. However, the compressive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 19 publications
1
15
0
2
Order By: Relevance
“…Unfortunately, very few research papers in the concrete industry have discussed how the tailings are dried. Only Onuaguluchi et al [53,54] describes that the tailing samples were air dried and then sieved with a 600 µm sieve. Other researchers [55] suggested that the tailings only passed a 45µm square hole sieve as a treatment method before it was used.…”
Section: Treatment Of Tailingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, very few research papers in the concrete industry have discussed how the tailings are dried. Only Onuaguluchi et al [53,54] describes that the tailing samples were air dried and then sieved with a 600 µm sieve. Other researchers [55] suggested that the tailings only passed a 45µm square hole sieve as a treatment method before it was used.…”
Section: Treatment Of Tailingsmentioning
confidence: 99%
“…By using calcined tailings in which metakaolin was created from the kaolinite, the compressive strength of concrete improved and had a maximum with an optimum concentration of tailings [35,62]. When the tailings as an additive were not a replacement of cement, the compressive strength of concrete with tailings was higher than the control concrete owing to the filler effect [54,74].…”
Section: Effect On Hardened Propertiesmentioning
confidence: 99%
“…Future recommendations about copper slag concrete are also included. Obinna Onuaguluchi et al [18] (2012), suggested in the results of an experimental study on various corrosion and durability tests on concrete containing copper slag as partial replacement of sand and cement. For this research work, M20 grade concrete was used and the tests were conducted for various proportions of copper slag replacement with sand of 0%,20%,40% and 60%,cement of 0%,5%,15% and 20% in concrete.…”
Section: B Recycled Aggregatementioning
confidence: 99%
“…Higher impact velocity induces higher coating density and stronger bonding force of the flat particles. Therefore, it is more significant to investigate their deformation and solidification of droplets with a high impact velocity [12][13][14] . In this paper, the volume of fluid method is adopted to track the free surface and the interface of the collision between the droplet and the substrate.…”
Section: Introductionmentioning
confidence: 99%